Population Dynamics of the Terrestrial - Isopod species Armadillidium vulgare Latrielle , 1804 in AL - Jadriyia District -Baghdad - Iarq . - Baghdad Science Journal (مجلة بغداد للعلوم, 2011)
The Present Work includes the study of the population dynamics of Armadillidium vulgare in AL- Jadiriya region in Baghdad. Monthly samples were collected using a quadrat 0.0625 m2 from November 2007 to November 2008.. The population density of A.vulgare, ranged from 880 ind/m2 in May to251 ind/m2 in January respectively. This species showed high aggregation dispersion in the study area. The sex ratio showed that the number of females were more than that of males and significantly differd (P < 0.05) during the reproductive months. Furthermore, it was found that the juveniles of species were present at most time of the year, But the large sized groups have been observed during summer and spring. And showed a positive linear correlations between the size of ovigerous females and the number of eggs and The incubation period ranged from 30 to 50 day in this species, The number of eggs per brood ranged between 9- 32 egg in this species. The cohort analysis of the populations showed that A.vulgare had three generations during the study period .The life table analysis results showed that the expected life for this species was six months. And this species had single breeding season started from April to September